Elevated-temperature Deformation Mechanisms in a CrMnFeCoNi High-Entropy Alloy. (1st October 2021) - Zhang, M.; George, E.P.; Gibeling, J.C.
Abstract: Stress reduction creep experiments were performed on a CrMnFeCoNi high-entropy alloy at 1073 K to characterize the steady-state and transient creep properties of this material. From measurements of constant-structure creep, the activation area for deformation of CrMnFeCoNi was determined to be ∼100 b 2 and to decrease with increasing applied stress, indicating the presence of both concentrated solid solution and forest dislocation control of high temperature plastic deformation. With the aid of a recent solid solution theory for high entropy alloys, quantitative separation of the two mechanisms was carried out using a Haasen plot and the results show that creep in CrMnFeCoNi relies heavily on thermal activation with the majority of creep strength coming from solid solution hardening, especially at low applied stresses. The overall analysis conducted in this study reveals that steady-state creep deformation of CrMnFeCoNi at 1073 K can be adequately described by existing concentrated solid solution hardening models and forest dislocation hardening models. This observation suggests it may be possible to develop a unified treatment of the dislocation glide kinetics for this alloy from cryogenic to elevated temperatures. Graphical abstract: Image, graphical abstract